The effects of breakfast consumption on concentrated and distributed attention levels: a cross-sectional study with Brazilian school children of the public school system - Freitas, Guilherme Nunes de; Mendes, Aluísio Menin; Foschiera, Diogo Bertella (Cuadernos de Psicología del Deporte, 2022)
Attention is a very important aspect for school performance; and, regular breakfast consumption has been associated with better student performance. In addition, adequate glycemia levels are related to better quality of life. Therefore, the purpose of this study is to analyze the effects of breakfast consumption and glycemia levels on concentrated and distributed attention levels of high school students. This is a quantitative and cross-sectional research. The sample was composed by 54 students with average ages of 16±0.89, regularly enrolled in high school at an institution of the public school system. For this research we used the following data collection instruments: I) food records; II) capillary blood glucose testing with electronic device; III) Toulouse-Piéron’s concentrated attention test, and; IV) Grid-type test. The data was collected on visits to the research site from 8:00 a.m. and 9:00 a.m. The sample was divided into fed group (who had breakfast) and fasting group (who had no breakfast). The fed group showed statistically better results for glycemia levels (87.25±14.76 mg/dl), concentrated attention (116.21±36.49 points), and distributed attention (20.89±4.08 points). Mild correlations between the glycemia and attention levels were found. The results suggest a positive association between breakfast consumption and glycemia levels adequate to health with concentrated and distributed attention levels.